Como fazer concordar a vida com os céus: magia e dissimulação em Marsílio Ficino - Vieira, Otávio Santana (2020)
Marsilio Ficino is an important name associated to the narratives involving ancient wisdom in the 15th century, which included the writings of Hermes Trismegistos, Zoroaster, Orpheus, Pythagoras, Plato and others. These sources and authorities were involved in the attempt to establish a new interpretation of Christianity and the origin of Religion. These sources reverberated in the philosophical, magical, and religious thought of the time, characterizing and constituting a form of knowledge that today is called esotericism. This classification involves not only literature, but ideas, notions, cosmological views, philosophical, magical, astrological, and theological conceptions. In this thesis we will investigate some ideas related to ancient wisdom, natural magic, astrology and their relations with an attitude that we designate as dissimulation involving the context of Florence and Italy in the second half of the 15th century. The dissimulatory attitude that we seek to characterize consists of an action of concealment, hiddenness or masking of intentions in the face of complex situations involving suspicion of heresy, association with prohibited books, astrological magic assumptions that are difficult to sustain and demonology. This problem is related to Christian antimagical thinking and its clash with pro-magic theories by authors like Ficino linked to natural magic and ancient wisdom as a risk of heresy. In this context, defending and concealing controversial adherences becomes a necessity to keep away from suspicions and accusations. In this way, this thesis reconstructs the fundamental elements of Fi magic in terms of theoretical and technical foundation, understanding its main ideas, notions, habits of thought and sources, analyzing the topics indicated as controversial and the dissimulatory attitudes presented in the De Vita Coelitus Comparanda (1489) and Apologia (1489), and the arguments and resources employed by Ficino in his attempt to demonstrate obedience to the church in its self-defense.